Stiffness Model of Rolling Bearing Considering Clearance and Analysis of Its Time-varying Characteristic - Runlin Chen; Qin Han; Menghao Zhang; Yanchao Zhang; Longlong Li; Yahui Cui (Jixie chuandong)
In order to research the influence of the time-varying stiffness of rolling bearings on the precision of spindle rotation of machine tools， a time-varying stiffness model of rolling bearings are established by considering the radial clearance. And the average stiffness and stiffness amplitude change rate are proposed to characterize the time-varying characteristics of stiffness. Taking deep groove ball bearings as an example， the influences of different radial clearances， loads， and numbers of bearing rolling elements on the time-varying stiffness of rolling bearings are analyzed. The results show that the average stiffness of the bearing is negatively related to the radial clearance and positively related to the load and the number of rolling elements； the stiffness amplitude change rate generally increases with the increase of the radial clearance， and decreases with the increase of the load and the number of rolling elements. But when the number of equivalent bearing rolling elements is an integer， the time-varying characteristics of rolling bearing stiffness are the most significant. In order to reduce the time-varying characteristics of bearing stiffness， a reasonable clearance and number of rolling elements should be selected according to the working conditions such as load and speed.